Bioequivalence Study of Clopidogrel Bisulfate Film-coated Tablets - Lainesse, Audrey; Ozalp, Yildiz; Wong, Hong; Alpan, Recep Serdar (Arzneimittelforschung, 2004)
The aim of the present study was to evaluate the bioequivalence of two Clopidogrel (CAS 120202-66-6) formulations. The study was performed according to an open, cross-over design in one study center in 36 healthy male and female volunteers, comparing a new generic product (tablets containing Clopidogrel bisulfate, 75 mg) with the originator product (reference). In each of the two study periods (separated by a wash-out of 7 days) a single dose of 150 mg (test or reference) was administered. Blood samples were taken up to 48 h post dose, the plasma was separated and the concentrations of Clopidogrel were determined by an LC/MS/MS method. AUC0–inf, AUC0–t, Cmax, Tmax and T1/2 el were calculated for both formulations.The mean AUC0–inf, AUC0–t and Cmax were 29.94 ng · h/mL, 29.53 ng · h/mL and 7.386 ng/mL, respectively, for the test formulation and 29.24 ng · h/mL, 28.83 ng · h/mL and 7.921 ng/mL, respectively, for the reference formulation. The median Tmax for both formulations was 1.25 h. The point estimators of the ratios test/reference formulation for AUC0–inf, AUC0–t and Cmax were 101.17%, 101.13 % and 90.96 %, respectively. Furthermore, the 90 % geometric confidence intervals of the mean ratio of In-transformed AUC0–inf and AUC0–t were narrow and symmetrical around 100 %, i.e. from 96.38 % to 106.21 % for AUC0–inf and from 96.20 % to 106.30 % for AUC0–t, whereas the confidence interval for Cmax was 84.07 % to 98.41 %.In can be concluded that the two Clopidogrel formulations (test formulation of Clopidogrel bisulfate and reference formulation) are bioequivalent in terms of the rate and extent of absorption.
Keywords: CAS 120202-66-6; Clopidogrel, bioequivalence, clinical pharmacokinetics